The Preperitoneal Space in Hernia Repair - Lorenz, A.; Augustin, C.; Konschake, M.; Gehwolf, P.; Henninger, B.; Augustin, F.; Öfner, D. (Frontiers in Surgery, 2022)
The preperitoneal spaces relevant for incisional hernia repair and minimally invasive groin hernia repair a described in terms of surgical anatomy. Emphasis is put on the transversalis fascia and the urogenital fascia and its extensions, the vesicoumbilical fascia and the spermatic sheath of Stoppa. Steps in hernia surgery where these structures a relevant are reviewed.